Keberadaan Komisaris Independen dalam Menerapkan Good Corporate Governance pada Perseroan Terbatas - Safiratul Ummah; Eva Dwi Nur Aini; Sumriyah Sumriyah (International Forum of Researchers and Lecturers, 2024)
The existence of an Independent Commissioner in a Limited Liability Company (PT) is a crucial element in realizing Good Corporate Governance (GCG). The role of the Independent Commissioner is not only as a supervisor, but also as a balancer of the interests of shareholders, management and other related parties. So with this Independent Commissioner, transparency, accountability and company integrity can be improved. This explains how the role of the Independent Commissioner makes a positive contribution to the company's sustainability and stakeholder trust, company reputation, and creates a healthy and sustainable business environment. So, the existence of an Independent Commissioner is not just a formality, but the main key in realizing Good Corporate Governance (GCG) practices in Limited Liability Companies.